2020
DOI: 10.2174/1567201817666200810110226
|View full text |Cite
|
Sign up to set email alerts
|

Alginate as Promising Natural Polymer for Pharmaceutical, Food, and Biomedical Applications

Abstract: : Alginates are biopolymers usually obtained from brown seaweed, brown algae (Ochrophyta, Phaeophyceae), and bacteria (Azatobacter vineland and Pseudomonas species) belonging to the family of polycationic copolymers. They are biocompatible, biodegradable, non-antigenic, and non-toxic biopolymer with molecular mass ranges from 32,000-40,000 g/mol in commercial grades. These can be used as edible films or coatings in food industries and also some natural or chemical additives could be incorporated into them to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 116 publications
0
27
0
Order By: Relevance
“…The brown seaweed, Saccharina japonica, accounts for more than one-third of total world production, with over 11 million tonnes in 2018 [3]. Brown seaweeds have many commercial uses, including as food for human consumption [4], improving growth and meat quality of livestock [5], as a substrate for bioethanol production [6], as biostimulants for agricultural use [7] and as cation exchangers for wastewater remediation [8]. Further, the management of metabolic syndrome may be improved by some brown seaweeds, including Ascophyllum nodosum and Fucus vesiculosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…The brown seaweed, Saccharina japonica, accounts for more than one-third of total world production, with over 11 million tonnes in 2018 [3]. Brown seaweeds have many commercial uses, including as food for human consumption [4], improving growth and meat quality of livestock [5], as a substrate for bioethanol production [6], as biostimulants for agricultural use [7] and as cation exchangers for wastewater remediation [8]. Further, the management of metabolic syndrome may be improved by some brown seaweeds, including Ascophyllum nodosum and Fucus vesiculosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial mechanism of ZnO was explored through in vitro antibacterial tests, and the healing results of burn wounds in rats indicated that the dressing has a certain burn treatment effect ( Figure 5 D). Other natural polymer materials commonly used for electrospinning wound dressings include alginate [ 109 ], collagen and cellulose.…”
Section: Electrospun Nanofibers In Wound Dressingmentioning
confidence: 99%
“…Excipients, particularly polymeric excipients, have played a fundamental role in the modification of drug release profiles over the past half a century [50][51][52]. For example, hydrophilic polymers and hydrophobic polymers greatly support the development of fastrelease and sustained-release profiles [53][54][55], respectively. Certainly, these polymers need a suitable technique to encapsulate the drug molecules that they contain.…”
Section: Introductionmentioning
confidence: 99%